2018
DOI: 10.1002/gps.4845
|View full text |Cite
|
Sign up to set email alerts
|

Goal‐orientated cognitive rehabilitation for dementias associated with Parkinson's disease―A pilot randomised controlled trial

Abstract: Cognitive rehabilitation is feasible and potentially effective for dementias associated with Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(75 citation statements)
references
References 47 publications
(65 reference statements)
2
71
1
1
Order By: Relevance
“…In this study, the participants were randomly assigned into three groups: 10 people received cognitive rehabilitation, 10 relaxation therapies, and 9 received traditional medicine therapy. The results of this study showed that cognitive rehabilitation improved depression more effectively than other therapies [9]. In this study, the effect of cognitive rehabilitation intervention on depression has been investigated and the memory rehabilitation program (memorization and recall memories) has been used, which is in line with the current study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this study, the participants were randomly assigned into three groups: 10 people received cognitive rehabilitation, 10 relaxation therapies, and 9 received traditional medicine therapy. The results of this study showed that cognitive rehabilitation improved depression more effectively than other therapies [9]. In this study, the effect of cognitive rehabilitation intervention on depression has been investigated and the memory rehabilitation program (memorization and recall memories) has been used, which is in line with the current study.…”
Section: Discussionsupporting
confidence: 53%
“…The cognitive rehabilitation program (CRP) is one of the efficient ways to improve the psychological problems of the elderly. CRP involves a complicated set of techniques that strive to reinforce or re-establish old patterns, initiate new behavioral patterns, or present a mechanism that aspires to compensate for the cognitive dysfunctions of the damaged nervous system [9].…”
Section: Introductionmentioning
confidence: 99%
“…Continuous care should ideally be provided by physicians experienced in the complex management of these patients. Other than pharmacological management, persons with DLB might also benefit from counselling, psychological support or goal-oriented rehabilitation,48 particularly since this study has demonstrated the use of coping strategies to manage disease-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that, although the trained cognitive tasks improve in the short term, improvements do not necessarily generalize to daily task performance (29,30). The few cognitive rehabilitation studies that suggest short-term beneficial effects on daily life include components of strategy or transfer training (31)(32)(33)(34). The outcome of improvement in daily functioning in these studies was assessed with patient-reported outcome measures.…”
Section: Discussionmentioning
confidence: 99%